Familial idiopathic cerebral calcifications. Issue 3 (March 1977) - Boller, F; Boller, M; Gilbert, J
Abstract : Nine members of a family spanning three generations showed bilateral calcifications of the basal ganglia with autosomal dominant inheritance. Two members developed chorea, dementia, and a characteristic speech disturbance (palialalia) in the third or fourth decade. A third member possibly shows the initial stage of a similar syndrome. Six members with calcifications but without neurological signs are younger than 25 years. All nine patients had normal calcium and phosphorus, and no evidence of endocrinological or somatic abnormalities. Thie 'isiopathic' picture must be differentiated from hypoparathyroidism and pseudohypoparathyroidism.